Pensekuritian Bersandarkan Aset Secara Islam - Nadhirah, Nordin; Mohamad Sabri, Haron (2008)
The paper discusses the definition, development, concept, structure of Islamic Asset-Backed Securities (ABS) and its practice in Malaysia. It focuses on the Syariah principles that are agreed upon and those that are disagreed upon by Syariah scholars in structuring the Islamic ABS. This article also mentions the application of the Syariah principles in ABS securities in Malaysia and to the extent of its compliance with the methodologies and principles under the Islamic perspective.